Comparative Analysis of the Vowel System of the Modern Literary (Standard) Croatian Language and the Vowel Systems of Modern Eastern-Slavic Literary Languages - Попович, Миленко; Тростинська, Раїса Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article compares the vowel system of the contemporary Croatian standard language and the vowel systems of contemporary East Slavic languages on the synchronic level (occasionally references the diachronic level as well), it points out similarities and differences in the realization of vowel and consonant syllabic liquid phonemes, inherited from Proto-Slavic.